2002
DOI: 10.1016/s1097-2765(02)00500-2
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Sparing in the Yeast Proteome in Response to Sulfur Demand

Abstract: Genome-wide studies have recently revealed the unexpected complexity of the genetic response to apparently simple physiological changes. Here, we show that when yeast cells are exposed to Cd(2+), most of the sulfur assimilated by the cells is converted into glutathione, a thiol-metabolite essential for detoxification. Cells adapt to this vital metabolite requirement by modifying globally their proteome to reduce the production of abundant sulfur-rich proteins. In particular, some abundant glycolytic enzymes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
243
4
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(284 citation statements)
references
References 37 publications
32
243
4
5
Order By: Relevance
“…These experiments demonstrated up-regulation of proteins involved in the sulfur amino acid biosynthesis pathway, indicating the need to replace damaged proteins containing the sulfur amino acids methionine and cysteine. Interestingly, similar studies that analyzed the response to hydrogen peroxide-induced oxidative stress showed a striking difference between the cadmium and the oxidative stress response because a small decrease of sulfur amino acid pathway components was observed in response to hydrogen peroxide (Godon et al, 1998).Cadmium exposure of yeast also induces expression of several isozymes of the carbohydrate metabolism such as pyruvate decarboxylase, enolase, and aldehyde dehydrogenase (Fauchon et al, 2002). All the cadmium-induced isozymes showed markedly reduced sulfur content, that is, less methionine and cysteine residues compared with the enzymes expressed under nonstress conditions.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…These experiments demonstrated up-regulation of proteins involved in the sulfur amino acid biosynthesis pathway, indicating the need to replace damaged proteins containing the sulfur amino acids methionine and cysteine. Interestingly, similar studies that analyzed the response to hydrogen peroxide-induced oxidative stress showed a striking difference between the cadmium and the oxidative stress response because a small decrease of sulfur amino acid pathway components was observed in response to hydrogen peroxide (Godon et al, 1998).Cadmium exposure of yeast also induces expression of several isozymes of the carbohydrate metabolism such as pyruvate decarboxylase, enolase, and aldehyde dehydrogenase (Fauchon et al, 2002). All the cadmium-induced isozymes showed markedly reduced sulfur content, that is, less methionine and cysteine residues compared with the enzymes expressed under nonstress conditions.…”
mentioning
confidence: 96%
“…Rather than by direct DNA damage, cadmium leads to genome instability by inhibition of the DNA mismatch repair system (Jin et al, 2003). Although the mechanism of how cadmium inhibits DNA repair is not clear, it has been suggested that damage of sulfhydryl groups containing components of the mismatch repair system might be responsible (Jin et al, 2003).The damaging effect of cadmium on sulfhydryl groups containing proteins also is reflected in gene expression profiling experiments and proteome analyses in response to cadmium exposure (Vido et al, 2001;Fauchon et al, 2002). These experiments demonstrated up-regulation of proteins involved in the sulfur amino acid biosynthesis pathway, indicating the need to replace damaged proteins containing the sulfur amino acids methionine and cysteine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first dimension separation can be performed with either carrier ampholites or immobilized pH gradients. Proteins may be stained with chemical dyes (such as Coomassie Blue [12][13] or silver nitrate [14]), labelled with radioactive isotopes ( 3 H, 14 C, 35 S, 32 P) [15][16][17], or revealed by fluorography. Using phosphor screen technology, one can label differently the proteome in two different conditions by growing cells on two isotope media, such as 3 H and 35 S [18], or 3 H and 14 C [19], and compare the relative values of each signal.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the difference gel electrophoresis (DIGE [20]) is based on the differential incorporation of two fluorescent cyanine dyes. Various software packages have been developed for protein quantification [21], and have been used to study a large range of biological processes in various species, such as physiological changes due to environmental stress [15][16][17]22] or to development [12,14]. In genetics, proteins have been used to reveal variability between species [23] or genotypes [12][13][24][25][26].…”
Section: Introductionmentioning
confidence: 99%